As percepções dos pais diante da síndrome de down do filho e o cotidiano dessas famílias - Cavalheiro, Noemia da Silva (2016)
The aim of this study was to describe the perceptions of parents on Down syndrome child and the daily life of these families. To this end, semi-structured interviews were conducted with 8 couples, parents of babies with clinical diagnosis of Down syndrome. These interviews were conducted in two phases with the same fathers and/or mothers: before receiving the results of Karyotype and 2 months after having received this result. The material obtained was analyzed by content analysis and after a first reading of this material did analysis from the following categories: 1st stage-a) clinical diagnosis of Down syndrome, having as a subcategory a1) perceptions about child syndrome; 2nd phase-a) the daily lives of families after the laboratory result, containing subcategories a1) and child care routine with DS and a2) familiar everyday experiences; and b) future perspectives for the son with DS. Through this analysis, it was possible to observe that the way the news of child syndrome is given interferes with the way parents react. In addition, although all families have passed through the expectation of waiting for laboratory results and feel shaken, after this result were seeking the best for the health, learning and development of their children, so that they achieve autonomy as any citizen.